IL-10 Overexpression After BCG Vaccination Does Not Impair Control of Mycobacterium tuberculosis Infection - Ferreira, Catarina M.; Micheli, Consuelo; Barreira-Silva, Palmira; Barbosa, Ana Margarida; Resende, Mariana; Vilanova, Manuel; Silvestre, Ricardo; Cunha, Cristina; Carvalho, Agostinho; Rodrigues, Fernando; Correia-Neves, Margarida; Castro, António Gil; et al. (Frontiers in Immunology, 2022)
Control of tuberculosis depends on the rapid expression of protective CD4+ T cell responses in the Mycobacterium tuberculosis (Mtb) infected lungs. We have recently shown that the immunomodulatory cytokine IL-10 acts intrinsically in CD4+ T cells and impairs their parenchymal migratory capacity thereby preventing control of Mtb infection. Herein, we show that IL-10 overexpression does not impact the protection conferred by the established memory CD4+ T cell response, as BCG-vaccinated mice overexpressing IL-10 only during Mtb infection display an accelerated, BCG-induced, Ag85b-specific CD4+ T cell response and control Mtb infection. However, IL-10 inhibits the migration of recently activated ESAT-6-specific CD4+ T cells into the lung parenchyma, and impairs the development of ectopic lymphoid structures associated with reduced expression of the chemokine receptors CXCR5 and CCR7. Together, our data support a role for BCG vaccination in preventing the immunosuppressive effects of IL-10 in the fast progression of Mtb infection, and may provide valuable insights on the mechanisms contributing to the variable efficacy of BCG vaccination.